Tuberous sclerosis complex: description of a family case of three brothers with phenotypic variability. - Mun, A.V.; Nizamova, D.F.; Kobiljonova, D.S.Q. (European Journal of Pediatric Dermatology, 2025)
Tuberous sclerosis complex (TS) is a rare autosomal dominant disease caused by mutations in the TSC1 or TSC2 genes, leading to dysregulation of the mTORC1 signaling pathway. This results in the development of benign tumors and hamartomas in various organs, including the skin, brain, kidney, lung, and heart. This study presents a unique case of three siblings with TS, highlighting the phenotypic variability of the disease within a single family. The eldest brother had prominent dermatological features and mild neurological symptoms, while the middle brother had severe neurological impairment despite milder skin involvement. The youngest brother had minimal manifestations, including limited skin lesions and attention deficit, but no seizures. These findings highlight the complexity of TS, underscoring the need for individualized and multidisciplinary management approaches. Early diagnosis and targeted therapies, such as mTOR inhibitors, are critical to improve the prognosis and quality of life of affected individuals.